Supporting AICCRA in the Organization and Facilitation of a Hackathon in West Africa - Barret Dia, Héloïse; Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report provides a deep dive on the Sen AgriHack 2023, the innovation challenge organized by AICCRA to address post-harvest losses in Senegal. Through Sen AgriHack 2023, AICCRA created a dynamic platform for interdisciplinary collaboration among participants and stakeholders to generate relevant solutions to challenges faced by farmers and value chain actors. The event also included a capacity building component on climate change and its impacts, gender responsive-csa, post harvest management provided by CGIAR experts. Through this approach, AICCRA was able to foster an environment conducive to transformative discussions and tangible outcomes